2019
DOI: 10.1021/acs.iecr.9b05073
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Highly Selective Ratiometric Fluorescence Probe Based on Benzo[5]helicene for the Detection of Hypochlorous Acid

Abstract: In physiological processes, hypochlorous acid can regulate in vitro signaling molecules as one kind of reactive oxygen species (ROS). Serious diseases, such as cardiovascular disorders, neurodegenerative diseases, Alzheimer’s disease, and cancers are usually concerned with the abnormal levels of hypochlorous acid in human bodies. Herein, we report a new probe DPH-BP for HClO, which consists of a benzo[5]­helicene-pyridine fluorophore and benzyl-benzeneboronic acid pinacol ester as HClO reaction sites. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…5A inset), indicating the fast response of HQ to HOCl. [41][42][43][44][45][46][47] Effects of pH on HQ's emission and its uorescence response to HOCl were also investigated in the presence and absence of HOCl. As shown in Fig.…”
Section: Spectroscopic Responses Of Hq To Hoclmentioning
confidence: 99%
“…5A inset), indicating the fast response of HQ to HOCl. [41][42][43][44][45][46][47] Effects of pH on HQ's emission and its uorescence response to HOCl were also investigated in the presence and absence of HOCl. As shown in Fig.…”
Section: Spectroscopic Responses Of Hq To Hoclmentioning
confidence: 99%
“…[5b,7] As one of reactive oxygen species (ROS), hypochlorous acid/hypochlorite (HClO/ClO À ) in organism is usually generated through enzyme-catalyzed oxidation reaction between chloride and hydrogen peroxide in activated phagocytes under the assistance of myeloperoxidase (MPO). [8,9] It is a double-edged sword for organisms, because it not only plays an important role in many biological processes as an important intracellular signaling molecule, [10] but also is associated with pathogenesis of various diseases, [11] so the hypochlorous acid. For instance, it is found that the abnormal accumulation of HClO can cause extensive oxidative stress [12] and oxidative damage in human neurodegenerative diseases and further induce a series of diseases including atherosclerosis, [13] rheumatoid rheumatism, [14] cancer, [15] reperfusion injury, [16] ischemia and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many new progress about the application of ROS in disinfection has also been reported [5b,7] . As one of reactive oxygen species (ROS), hypochlorous acid/hypochlorite (HClO/ClO − ) in organism is usually generated through enzyme‐catalyzed oxidation reaction between chloride and hydrogen peroxide in activated phagocytes under the assistance of myeloperoxidase (MPO) [8,9] . It is a double‐edged sword for organisms, because it not only plays an important role in many biological processes as an important intracellular signaling molecule, [10] but also is associated with pathogenesis of various diseases, [11] so the hypochlorous acid.…”
Section: Introductionmentioning
confidence: 99%
“…There was no interaction between 2,6-dimethoxyanthracene and G because of almost no change in fluorescence. To quantitatively study the binding affinity, fluorescence titration experiments were performed to determine the association constants ( K a ) . Pagoda­[ n ]­arenes showed strong blue fluorescence, and the electron deficient tropylium could quench the fluorescence effectively.…”
mentioning
confidence: 99%